Psychological Well-Being Among Employees of PT Supra Natami Utama, Sukabumi City: A Descriptive Study - Chairunnisa; Nurwahyuni Nasir; Hema Dayita Pohan (Journal of Health and Multidisciplinary Health Studies, 2026)
Psychological well-being is an essential aspect of employees' mental health and optimal functioning in the workplace. Understanding employees' psychological well-being is important for promoting a healthy and productive work environment, particularly in the manufacturing sector. This study aimed to describe the psychological well-being of employees at PT Supra Natami Utama, Sukabumi City. A quantitative descriptive research design was employed involving 158 employees selected through stratified random sampling from a population of 261 employees. Data were collected using an adapted version of Ryff's Psychological Well-Being Scale (RPWBS). The instrument demonstrated acceptable psychometric properties, with 10 valid items and a Cronbach's alpha coefficient of 0.735. Data were analyzed using descriptive statistics, including the mean, standard deviation, frequency, and percentage. The findings showed that the overall mean psychological well-being score was 42.93 (SD = 3.477). Based on the hypothetical norm categorization, 93.7% of participants were classified as having high psychological well-being, while 6.3% were categorized as having moderate psychological well-being, and no participants were classified in the low category. Furthermore, both daily and monthly employees were predominantly classified in the high psychological well-being category, with monthly employees showing a slightly higher proportion than daily employees. These findings indicate that employees at PT Supra Natami Utama generally demonstrate positive psychological functioning. The study provides empirical evidence regarding employees' psychological well-being in the Indonesian manufacturing sector and offers practical insights for organizations in maintaining workplace environments that support employees' psychological health.